What do Cochrane systematic reviews say about interventions for treating psoriasis? - Pacheco, Rafael Leite (2018)
CONTEXT AND OBJECTIVE: Psoriasis is a common chronic inflammatory skin disease characterized by abnormal and increased growth of the cells that produce keratin and abnormal functioning of the immune system. We aimed to summarize the evidence available regarding interventions for patients with psoriasis. DESIGN AND SETTING: Review of systematic reviews, developed in the Discipline of Evidence-Based Medicine, Escola Paulista de Medicina, Universidade Federal de São Paulo. METHODS: A systematic search was conducted to identify Cochrane systematic reviews that fulfilled the eligibility criteria. Two authors screened titles and abstracts that had been retrieved through the search strategy. The results from all the Cochrane systematic reviews that were included were summarized and presented in a narrative synthesis. RESULTS: We included six Cochrane systematic reviews assessing interventions for treating psoriasis. The findings from high-quality evidence were that (a) etanercept reduced the psoriasis severity index, compared with placebo and (b) steroids plus vitamin D, compared with vitamin D alone, improved the skin clearance rate, as assessed by investigators, but was associated with a higher proportion of participants who dropped out due to adverse events. For all other comparisons, the quality of the evidence ranged from moderate to very low. CONCLUSION: This review included six Cochrane systematic reviews that provided evidence ranging in quality from unknown to high, regarding management of psoriasis. Further randomized controlled trials are imperative to reduce the uncertainties relating to several treatments that are already used in clinical practice.